Highly Efficient Electrocatalytic N2 Reduction to Ammonia over Metallic 1T Phase of MoS2 Enabled by Active Sites Separation Mechanism. Issue 2 (5th November 2021) - Liu, Ruoqi; Guo, Ting; Fei, Hao; Wu, Zhuangzhi; Wang, Dezhi; Liu, Fangyang
Abstract: The 1T phase of MoS2 has been widely reported to be highly active toward the hydrogen evolution reaction (HER), which is expected to restrict the competitive nitrogen reduction reaction (NRR). However, in this work, a prototype of active sites separation over 1T‐MoS2 is proposed by DFT calculations that the Mo‐edge and S atoms on the basal plane exhibit different catalytic NRR and HER selectivity, and a new role‐playing synergistic mechanism is also well enabled for the multistep NRR, which is further experimentally confirmed. More importantly, a self‐sacrificial strategy using g‐C3 N4 as templates is proposed to synthesize 1T‐MoS2 with an ultrahigh 1T content (75.44%, named as CNMS, representing the composition elements of C, N, Mo, and S), which yields excellent NRR performances with an ammonia formation rate of 71.07 µg h –1 mg –1 cat. at −0.5 V versus RHE and a Faradic efficiency of 21.01%. This work provides a promising new orientation of synchronizing the selectivity and activity for the multistep catalytic reactions. Abstract : A prototype of active sites separation over 1T‐MoS2 is proposed in which the Mo‐edge and S atoms exhibit different catalytic NRR and HER selectivity. Benefiting from the active site separation, the 1T phase can accelerate both NRR and HER, but prefer the former, thus achieving the synchronization of selectivity and activity toward the NRR.